Materia medica e naturalismo no império português no século XVI: a percepção da natureza indo-oriental no colóquios dos simples (Goa, 1563), de Garcia de Orta - Ribeiro Filho, Ronaldo Crispim (2020)
This is a historical investigation into the work Colloquies on the simples (Goa, 1563) by the Portuguese physician Garcia de Orta. It’s a work of pharmacy and natural history that sought to describe and incorporate the drugs and materials of the Indo-Oriental nature known to the 16th century naturalist during his nearly thirty years of experience and observation in the Estado da India. This study try to understand how these written and oral knowledge were confronted in the work by the author’s experience, producing new understandings about exotic nature. These knowledges were constructed in a dialogue format in portuguese, in context of the portuguese Renaissance, when the literate culture and Sciences were marked by the action of two forces: the circulation of humanist ideas and currents further the impact of discoveries and conquests in the seas. Thus, it was investigate wich roles and functions that this scientific work had in nascent modern court society, formed by nobles, clergymen, king’s officers, orators, academics, naturalists, navigators and literate physicians.